1975
DOI: 10.1002/oms.1210100813
|View full text |Cite
|
Sign up to set email alerts
|

Combined deuterium labeling and appearance potential measurements to uncover competing reaction mechanisms in the electron‐impact‐induced loss of water from cyclohexanol

Abstract: The appearance potentials for loss of H,O and DOH from the constitutional isomers 3,5-dideuterocyclohexanol and 4,4-dideuterocyclohexanol show, in agreement with proposals based on stereoselectivities, that 1,3 loss of water is energetically more costly than 1,4 loss of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…239 The conformations of sparteine group of alkaloids have been determined by X-ray crystallographic studies. Crystals of 7-hydroxy-/3-isosparteine perchlorate (224) are found to be orthorhombic, with space group P2i2t2i.24°T he unit cell dimensions are a = 13.04, b = 13.19, c = 9.59 A. The number of molecules in unit cell is 4. The molecule is called by convention241,242 trans,trans (while a-isosparteine is called cis,cis and sparteine is cis,trans), and all four of the six-membered rings are found to be in chair conformation.…”
Section: X-ray Crystallographymentioning
confidence: 99%
See 1 more Smart Citation
“…239 The conformations of sparteine group of alkaloids have been determined by X-ray crystallographic studies. Crystals of 7-hydroxy-/3-isosparteine perchlorate (224) are found to be orthorhombic, with space group P2i2t2i.24°T he unit cell dimensions are a = 13.04, b = 13.19, c = 9.59 A. The number of molecules in unit cell is 4. The molecule is called by convention241,242 trans,trans (while a-isosparteine is called cis,cis and sparteine is cis,trans), and all four of the six-membered rings are found to be in chair conformation.…”
Section: X-ray Crystallographymentioning
confidence: 99%
“…It has been clearly demonstrated that any one abstractable secondary hydrogen must be present within 1.8 A from the HO+ in order that H20 is eliminated. [224][225][226][227] The proximity effect could not be made use of for determining configurations of 9-substituents in chair-chair conformations. However, in boat-chair or chair-boat conformations use of this technique is possible.…”
Section: R=ch2dtsmentioning
confidence: 99%